Reinforced concrete building design project & project based learning (case study) - Zulkarnain, Muhammad Azri (2019)
Manual calculation was used to determined suitable size of critical structural member size only. This method is not really economical since only one size is applied throughout all related structural members. As an example, if a beam only loaded with minimum load, a critical size of beam will be applied. It is very complicated for an engineer to calculate on each particular beam. Therefore, esteem software was introduced. This is to ease the engineers work and produce more economical and might be cheaper value of particular project. There are few differences were determined after finished with both manual calculation and esteem result of our RC Design Project. All the differences were affected by few reasons. One of the reasons is in manual calculation, we only calculate on critical structural members. While in esteem, the calculations and result were shown precisely through each structural members. This is to helps in produce more economical value of a particular project. Which we only increase the structural members size that are failed. Moreover, all the data such as permanent and variable action were inserted separately depends on the particular member. Other than that, at a first place, we did draw structural drawing manually and simply assign few unnecessary structural members especially column. During running esteem, we are about to design by using our manual drawn structural drawing, however, whenever we tried to running to obtain the results, it showed that few columns are not needed. Which might effect to uplift forces. This contribute in difference result between esteem and manual calculation. As for steel design project, we chose on designing elevated water tank. The design was calculated manually. In our course ECS358, we did not carry out any software to calculate on steel design. Therefore, the results are not compared with any other results